Management of Coaching Football Achievement at the Football Association of Indonesia of Alor Regency - Lengmani, Patris Lorensius; Soegiyanto, Soegiyanto; Wahyudi, Agung (Study Program Education and Sports, Postgraduate Universitas Negeri Semarang, 2022)
The issue addressed in this research is the PSSI organization's lack of concentration to the growth of football achievements in Alor Regency. The purpose of this study is to evaluate the management of planning, organizing, implementing, and controlling (POAC) in the Football Association of Indonesia Alor Regency's football achievement development. This study used a qualitative method and an ethnographic design to evaluate the POAC. The administrators, coaches, and athletes of PSSI Alor Regency were the subjects of this study. The data collection in this study were used observation, interviewing, and documentation. The data analysis refers to the process of collecting data, data reduction, presentation, and drawing conclusions. Result of this study: Planning was effective in this case because it has been adjusted to the management's needs and criteria. The organization is inadequate since the infrastructure, training programs, and money are still not appropriate. Implementation is difficult in this scenario due to a lack of infrastructure and financing that is still insufficient. Overall, oversight is adequate, but funding is inadequate due to the supervisory commission's failure to conduct routine supervision. Conclusions are as follows: it is adequate for planning, inadequate for organization, inadequate for implementation, and adequate for supervision. Benefits of research results for Alor Regency: PSSI Alor Regency Management to carry out science and technology planning, create data facilities and infrastructure, Trainers and Athletes to be more disciplined and continue to improve performance.